Pengaruh Efikasi Diri (Self Efficacy) dan Lokus Kendali (Lokcus Of Control) Terhadap Kinerja (Performance) Karyawan Toko Mok’s Sport Bekasi - Indri Guslina; Rita Mardiana (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of Self-Efficacy and Locus of Control on Employee Performance at Mok's Sport Bekasi store. This study uses a quantitative descriptive method. The sampling technique in this study was a saturated sample of 34 people. The data collection technique used a questionnaire, while the data analysis used the analysis of Simple Linear Regression and Multiple Linear Regression. The results of this study indicate that there is a positive and significant effect between Self-Efficacy (X1) and Locus of Control (X2) on Employee Performance (Y). Calculation results: 1) P-value (sign) > 0.05 means that H1 is rejected and H0 is accepted, meaning that there is no influence between Self-Efficacy (X1) on Employee Performance (Y) of 0.008 or 00.8%. 2) Obtained Pvalue (sign) <0.05, meaning that H0 is rejected and H1 is accepted, meaning that there is an influence between the Locus of Control (X2) on Employee Performance (Y) of 0.889 or 88.9%. 3) Obtained Pvalue (sign) <0.05, meaning H0 is rejected and H1 is accepted, meaning that there is an influence between Self-Efficacy (X1) and Locus of Control (X2) on Employee Performance (Y) of 0.896 or 89.6%. This it can be concluded that: simultaneously the effect of Self-Efficacy and Locus of Control has an influence on Employee Performance